The Impact of Manuscript Learning vs. Video Learning on a Surgeon's Confidence in Performing a Difficult Procedure - Reck-Burneo, Carlos A.; Dingemans, Alexander J. M.; Lane, Victoria A.; Cooper, Jennifer; Levitt, Marc A.; Wood, Richard J. (Frontiers in Surgery, 2018)
Introduction: Operative surgical videos are a popular educational resource, not commonly a part of a peer-reviewed article. We wanted to evaluate the impact of either reading a peer-reviewed manuscript or watching an operative video on a surgeon's confidence in performing a complex case. Methods: Pediatric surgeons and fellows were asked to complete an initial questionnaire to assess their confidence (formulated as a score) in the diagnosis and operative repair of anal stenosis and rectal atresia. Results: Of 101 pediatric surgeons and fellows, 52 (51%) were randomized into a “manuscript” group and 49 (49%) into a “video” group. The mean confidence before the intervention was the same in the two groups (6.4 vs. 6.6). Attending surgeons started with more confidence than trainees (7.1 vs. 5.3, p < 0.001). In the manuscript group, the average confidence increased to 7.7 (p = 0.005), and in the video group the average confidence increased to 7.9 (p = 0.001) globally. Trainees in the video group significantly improved their confidence to a score of 6.6 (p = 0.035), as did attending surgeons to 8.5 (p = 0.01). In the manuscript group, only attendings significantly improved their confidence by 1.5–8.3 (p < 0.001), whereas trainees did not with a difference of 1.3 (p = 0.194). When considering experience level, physicians who reported never having performed this surgery improved only by reading the manuscript (3.9–6.2) (p = 0.004), not by watching the video (5.4–6.6) (p = 0.106). Surgeons with experience doing this operation (>5 times) did not improve their confidence by reading the manuscript (p = 0.10), nor by watching the video (p = 0.112). Conclusion: Reviewing either a detailed manuscript or operative video on the surgical management of rectal atresia and anal stenosis demonstrated a significant increase in self-reported confidence. Trainees benefitted the most from operative videos, whereas experienced surgeons did not improve their confidence by reading the manuscript nor watching the video.